Effects of Dietary Scutellaria baicalensis Extract on Growth, Feed Utilization and Challenge Test of Olive Flounder (Paralichthys olivaceus) - Cho, S. H. (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2013)
Effects of dietary Scutellaria baicalensis extract (SBE) on growth, feed utilization and challenge test of olive flounder (Paralichthys olivaceus) were determined. Six hundred thirty fish averaging 5.0 g were distributed into 18, 180-L tanks. Six experimental diets were prepared in triplicate: SBE-0, SBE-0.5, SBE-1, SBE-2, SBE-3 and SBE-5 diets containing SBE at the concentrations of 0, 0.5, 1, 2, 3 and 5%, respectively. Fish were hand-fed to apparent satiation twice a day for 8 wks. At the end of 8-wk feeding trial, ten fish from each tank were infected by Edwardsiella tarda for challenge test. Survival and weight gain of fish were not affected by dietary concentrations of SBE. However, specific growth rate of fish fed the SBE-2 diet was higher than that of fish fed the SBE-0, SBE-1, SBE-3 and SBE-5 diets. Neither feed efficiency nor serum chemical composition of fish was affected by dietary concentrations of SBE. The cumulative mortality of fish fed the SBE-0 diet was 100% at 96 h after E. tarda infection, but 77 to 87% for fish fed the other diets. Dietary inclusion of 2% SBE appears to be recommendable to improve specific growth rate of fish and SBE had the potential to mitigate mortality of fish at E. tarda infection.